Thermal Oxidation Induces Lipid Peroxidation and Changes in the Physicochemical Properties and β-Carotene Content of Arachis Oil - Ayodeji Osmund Falade; Ganiyu Oboh (International Journal of Food Science)
This study sought to investigate the effect of thermal oxidation on the physicochemical properties, malondialdehyde, and β-carotene content of arachis oil. Pure arachis oil was heated for 20 mins with a corresponding temperature of 220°C. Thereafter, changes in the physicochemical properties (acid, iodine, and peroxide values) of the oil samples were determined. Subsequently, the level of lipid peroxidation was determined using change in malondialdehyde content. Then, the total carotenoid and β-carotene contents were evaluated using spectrophotometric method and high performance liquid chromatography, respectively. The results of the study revealed a significant increase (P<0.05) in the acid and peroxide values and malondialdehyde concentration of the heated oil when compared with the fresh arachis oil. In contrast, a significant decrease (P<0.05) was observed in the iodine value, total carotenoid, 13-cis-, 15-cis-, trans-, and 9-cis-β-carotene, and total β-carotene content of the heated oil. Hence, thermal oxidation induced lipid peroxidation and caused changes in the physicochemical properties and carotenoid contents of arachis oil, thereby reducing its nutritive value and health benefit. Therefore, cooking and frying with arachis oil for a long period might not be appropriate as this might lead to a loss of significant amount of the insignificant β-carotene in arachis oil.